Transition-metal-free C-S bond formation: a facile access to aryl sulfones from sodium sulfinates via arynes - Pandya, Virat G.; Mhaske, Santosh B. (Organic Letters, 2014)
Sulfones have been attractive targets for synthetic organic chemists owing to their immense applications in medicinal, material, and synthetic chemistry. In this context, an efficient transition-metal-free process has been demonstrated, wherein a broad range of alkyl/aryl/heteroaryl sodium sulfinates react with varyingly substituted aryne precursors (o-silyl aryl triflates) under mild reaction conditions to afford structurally diverse sulfones in good to excellent yields.

Divergent synthesis of oxindolylidene acetates and spirooxindolopyrrolidones from arynes - Pandya, Virat G.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel process for the preparation of various (E)-oxindolylidene acetates using arynes and carbamoylpropiolates has been developed. The utility of this protocol is also further extended to the one-pot synthesis of complex spirooxindolopyrrolidones. This method provides a milder and transition-metal-free access to both of the target scaffolds in moderate to good yields.

Construction of tetrahydrobenzo[f]quinoline scaffolds via polar [4+2]-Cycloaddition reaction with arynes as dienophiles - Pandya, Virat G.; Mhaske, Santosh B. (Tetrahedron Letters, 2022)
A transition-metal-free route has been developed for the direct synthesis of biologically significant tetrahydrobenzo[f]quinoline scaffolds. The reaction features polar [4 + 2] Diels-Alder cycloaddition reaction of arynes with a well-designed diene N-Boc protected vinyl tetrahydropyridine, followed by the isomerisation of the double bond leading to the formation of tetrahydrobenzo[f]quinoline scaffolds in good to moderate yields.
Keywords: Aryne; Diels-Alder; Diene; Tetrahydrobenzo[ f ]quinoline